Post-marketing sampling and testing programs for licensed medicinal products: a narrative review - Edvaldo Oliveira Neves; Paloma Michelle de Sales; Dâmaris Silveira (Universidade de São Paulo, 2022)
Abstract The globalization of the pharmaceutical market has enabled access to a considerable number of new medicinal products. Consequently, the circulation of substandard medicinal products has also increased. To minimize this problem, post-marketing quality sampling and testing programs are performed to monitor and confirm that the medicinal products available in the market meet appropriate quality requirements. In this review, the post-approval sampling and testing procedures of six regulatory authorities were compared with the goal of strengthening these market surveillance systems. Similarities were observed between the procedures adopted by different regulatory authorities. However, the agencies were not always transparent about the results of these monitoring procedures. A probable mismatch between the registration procedures and the quality requirements listed in official compendiums was observed, which resulted in dissonance and contradiction between the specifications approved by the regulatory authorities and those required in the pharmacopeias. Therefore, strengthening harmonization projects related to these activities can help minimize such difficulties.